Revitalizing an indigenous musical tradition: a study of Korankye's approach to sustaining the seperewa musical tradition - Agyefi, Papa Kow Mensah (College of Music, 2022)
The Intangible Cultural Heritage (ICH) convention of UNESCO is arguably the most powerful institutional voice in the field of conserving cultural practices on an international level. This initiative and other initiatives of UNESCO have become prominent guidelines and blueprints in international, national, and local policies since the Declarations of Masterpieces in 2001, 2003 and 2005 and the highly successful 2003 ICH Convention. There is a steadily increasing body of research on music cultures and their sustainability. Basically, sustainability is a set of mechanisms and acts in place in order to prevent humans from the destruction of resources in order to maintain an equilibrium that does not cause the quality of life of communities to decrease. However, there have been various contentions by many scholars as to what we mean by sustaining a musical tradition or culture. Scholars like Bell Yung (2009), Jeff Titon (2009), Baron Beardslee (2014) and others have argued that the romanticizing of these initiatives by UNESCO is not the best method as the initiatives themselves appear to have done more harm to cultural heritage than good. They suggest that other approaches should be explored to investigate the best ways to manage cultural heritage. It is in this vein that my research examines the role of Osei Kwame Korankye, one of the exponents of the seperewa tradition in Ghana, in sustaining the musical instrument and its tradition today. It explores his approach and how he uses multiple techniques in achieving this goal. I focus on his efforts as a seperewa player and a teacher of the instrument at the University of Ghana. Korankye's desire is to create and revitalize people's interests in the instrument and its praxis. He has taught the techniques of the instrument to foreigners and locals alike since 1994 when Professor J.H. Kwabena Nketia realized his importance as a cultural repository. Framed within the theoretical orientation of the capability approach, which seeks ways to enhance and understand possible range of choices, and the abilities of individuals as well as communities, I discuss ways in which Korankye's method leads to an intervention that addresses the sustenance of the seperewa. I argue that Korankye's model of sustaining the seperewa tradition is oriented towards the adaptation of music traditions to new performance contexts and teaching environments, hence he offers cultural communities a range of options to choose from rather than an imposed singular methodology.